Нефритовые четки: [приключения Эраста Фандорина] / Борис Акунин - Акунин Борис (Новый детективъ, 2008)
Экземпляры: РБ (20210113☮) / Инвентарный номер: 59863 / Цена: 20.00 / Авт.знак: А 44 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6